Building High-Quality Expert Database Datasets: Guangdong’s Practices in Leading AI Empowerment and the Development of a Unified National Market - Zheng, Jiong; Qiu, Haowei; Huang, Lihua (Innovative Applications of AI, 2025)
Against the backdrop of accelerating the development of a unified national market, standardization and digitization in the field of public resource transactions are critical steps. As a core element of bidding and tender activities, the data quality of the evaluation expert database directly impacts the efficiency and fairness of resource allocation. This paper takes the innovative practices of Guangdong Province’s comprehensive evaluation expert database data specification as a case study, delving into how systematic data governance can be employed to construct high-quality expert datasets. These datasets support application scenarios such as AI-driven random selection and evaluation assistance, thereby providing a solid foundation for building a high-standard and high-efficiency unified national market.